2016
DOI: 10.1088/0967-3334/37/5/r1
|View full text |Cite
|
Sign up to set email alerts
|

A practical guide to non-invasive foetal electrocardiogram extraction and analysis

Abstract: Non-Invasive foetal electrocardiography (NI-FECG) represents an alternative foetal monitoring technique to traditional Doppler ultrasound approaches, that is non-invasive and has the potential to provide additional clinical information. However, despite the significant advances in the field of adult ECG signal processing over the past decades, the analysis of NI-FECG remains challenging and largely unexplored. This is mainly due to the relatively low signal-to-noise ratio of the FECG compared to the maternal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
91
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 80 publications
0
91
0
2
Order By: Relevance
“…Noninvasive fetal electrocardiography (NI‐FECG) is a promising noninvasive fetal diagnosis and monitoring alternative, which presents a number of advantages: low cost, possibility of local analysis (no need of long distance referral for pregnant women), information on atrial and ventricular activity, motion estimation, and possibility of continuous long‐term remote monitoring. The results of recent studies have shown the ability of the NI‐FECG to provide an accurate estimate of the fetal heart rate . However, to date, the clinical usability of NI‐FECG has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive fetal electrocardiography (NI‐FECG) is a promising noninvasive fetal diagnosis and monitoring alternative, which presents a number of advantages: low cost, possibility of local analysis (no need of long distance referral for pregnant women), information on atrial and ventricular activity, motion estimation, and possibility of continuous long‐term remote monitoring. The results of recent studies have shown the ability of the NI‐FECG to provide an accurate estimate of the fetal heart rate . However, to date, the clinical usability of NI‐FECG has rarely been studied.…”
Section: Introductionmentioning
confidence: 99%
“…The results of recent studies have shown the ability of the NI-FECG to provide an accurate estimate of the fetal heart rate. [11][12][13][14][15][16] However, to date, the clinical usability of NI-FECG has rarely been studied. This work investigates the feasibility and interest for a fetal Holter ECG device in the context of fetal ARR detection.…”
Section: Introductionmentioning
confidence: 99%
“…NI-FECG demonstrates several advantages over ultrasound based cardiotocography (CTG) in that it is a passive modality suitable for long term use and may provide novel physiological information in addition to FHR [4]- [6]. As the ECG waveform aims to represent the magnitude and temporal characteristics of electrical currents within the cardiac muscle, morphological analysis of NI-FECG recordings has been proposed for identifying signs of fetal distress such as hypoxia and intrauterine growth restriction (IUGR) [7]- [9]. The process of morphological analysis can be divided into two distinct phases: 1) Extraction -the process of extracting a fetal ECG waveform from noisy single or multi-channel recordings and 2) Analysis -the process of analyzing features of the extracted ECG waveform to assess physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…A singlelead configuration is helpful for implementa-tion in a mini health care unit, making it suitable for ambulatory and long-term monitoring. [9].…”
Section: Introductionmentioning
confidence: 99%